DC super hero girls triple feature [videorecording (DVD)] - Fontana, Shea (DC super hero girls, 2018)
Legends of Atlantis Dive deep into adventure with the Super Heroes in an all new underwater epic. Sisters of the sea, Siren and Mera catch the students of Super Hero High offguard in a surprise attack to steal a very powerful relic, the Book of Legends. With the book in her possession and harnessing more power than ever, Siren aims to raise an army from the depths of the ocean's trenches. It's up to the Super Heroes to help Aquaman.